Slope Reinforcement Mechanism and Stability Analysis of Ophiopogon bodinieri Under Rainfall Conditions - GUO Jianjun; ZhangWei; CaoHeng; WuZhenwei (Renmin Zhujiang)
To explore the reinforcement effect of Ophiopogon bodinieri on soil, the reinforcement mechanism of O. bodinieri on the surface soil of the slope was expounded. The compaction effect of the roots of O. bodinieri on the soil was analyzed. A calculation method for increasing the shear strength of soil has been proposed. Based on ABAQUS, four different rainfall intensities of 0, 10, 15, and 20 mm/h were applied to the bare soil slope and the slope was reinforced by the roots. The displacement of slope surface soil and the security coefficient of slope under different rainfall conditions were analyzed. According to the results, O. bodinieri enhances the integrity of the surface soil and increases the compactness of the soil with the extrusion and anchoring effects of the roots and the spindle-shaped blocks at the end. During rainfall, the root system of O. bodinieri can effectively limit the displacement of the slope surface, so that the large displacement area is transferred to the rear of the slope top. With the increase in rainfall, the displacement limitation effect is more obvious. At the same time, the root system of O. bodinieri can also improve the security coefficient of the slope. As the rainfall gets larger, the increase gets slower. With a significant reinforcement effect on soil slopes, O. bodinieri is an excellent slope protection plant and can be used for three-dimensional vegetation network slope protection technology during heavy rainfall.